Optimalisasi Pengelolaan Data PSU Dan Kawasan Kumuh Melalui Sistem Basis Data Terintegrasi di Provinsi Kalimantan Tengah: Optimization Of PSU And Slum Area Data Management Through An Integrated Database System In Central Kalimantan Province - Vriono, Agus; Chandrawati , T. Brenda (Media Ilmiah Teknik Sipil, 2026)
The provision of Infrastructure, Facilities, and Public Utilities (PSU) is a fundamental component in the development of housing and habitable residential areas. However, the implementation of PSU development programs in Central Kalimantan Province faces challenges in transparency, limited access to accurate information, and partial data management systems that hinder comprehensive monitoring and evaluation processes. This research aims to describe the design, development, and implementationprocess of the Geo PSU System application as an integrated database capable of inventorying and analyzing PSU and slum area data comprehensively. The research method uses a qualitative approach with a case study on the Geo PSU System developed using the System Development Life Cycle (SDLC) model. The research results show that the Geo PSU System application successfully integrates tabular databases with interactive spatial visualization, equipped with role-based access control security features, and provides a user-friendly modern dashboard. Statistical data shows a high level of accessibility with 2,328 total visits, reflecting transparency of information to the public. It can be concluded that the implementation of the Geo PSU System is effective in accelerating data provision, improving analysis accuracy, and realizing transparent, accountable, efficient, and sustainable residential area management in Central Kalimantan Province.